Angioimmunoblastic T-Cell Lymphoma Diagnosed From Serous Effusion by Integration of Cytologic Features and Ancillary Studies. Issue 4 (6th March 2023) - Li, Jinnan; Zhu, Xianglan; Deng, Xueqin; Zhang, Wenyan; Jiang, Yong; Wan, Yin; Chen, Jie; Li, Cong; Liu, Weiping; Zhao, Sha; Su, Xueying
Abstract: Objectives: To explore the approach to the diagnosis of malignant serous effusion (SE) caused by angioimmunoblastic T-cell lymphoma (AITL). Methods: The clinical, cytomorphologic, immunophenotypic, and molecular features of 6 patients were summarized. Results: Clinically, SE caused by AITL was predominant in middle-aged and older male patients with multiple SEs and lymphadenopathy. Cytomorphology showed small to medium-sized, irregular lymphocytes with clear cytoplasm and mixed with various inflammatory cells and apoptosis. Hodgkin/Reed-Sternberg–like cells were detected in 2 of 6 cases. Furthermore, 2 patterns of cytomorphology were described for the first time. Flow cytometry revealed abnormal T-cell populations with loss of surface CD3 (3/4 cases) and CD7 (3/4 cases). In addition, B-cell populations lacking surface immunoglobulin (Ig) were identified in 2 of 4 cases. Immunocytochemical staining revealed expression of at least 2 T follicular helper markers. Epstein-Barr virus–encoded RNA (EBER)–positive cells were demonstrated in 4 of 5 cases. Clonal T-cell receptor γ chain rearrangement was detected in 6 cases, and 3 of them had concomitant clonal immunoglobulin gene rearrangement. Moreover, 2 cases revealed discrepant findings regarding IgH/Igκ rearrangements in cytohistologic correlation. Conclusions: This study broadens the morphologic spectrum of malignant SE caused by AITL and provides diagnostic criteria in routine practice.